The Effect Of Good Corporate Governance, Corporate Social Responsibility and Green Innovation On The Financial Performance Of The Petroleum Sub-Sector - Sakuntala, Hayudya Caesar; Cahyaningtyas, Fadilla; Fitriyani, Yuniar (Manajemen Multitalenta Indonesia, 2025)
This research investigates the consequence of Good Corporate Governance, Corporate Social Responsibility, and Green Innovation on Company Financial Performance. The sample used was 10 out of 18 excavation manufactures in the petroleum sub-sector listed on the IDX and a total of 40 observations were obtained for the 2020-2023 timeframe. The sample was persistent applying a purposive sampling technique.The research applied multiple linear regression techniques through SPSS for data analysis. The conclusions showed that there were no variables that influenced the financial performance of Petroleum sub-sector manufactures filed on the IDX.